2010
DOI: 10.1590/s1517-70762010000200024
|View full text |Cite
|
Sign up to set email alerts
|

A general study of commercially pure Ti subjected to severe plastic deformation: microstructure, strength and corrosion resistance

Abstract: Bars of Titanium Grade 2 were subjected to deformation by Equal Channel Angular Pressing, both at room temperature and at 300°C. Additionally, some specimens were cold rolled up to 70% reduction. From tensile tests, data such as yield, maximum strength, elongation and area reduction were obtained. Results show that the best strength-ductility combination is produced by four passes followed by cold rolling. Finally, the corrosion behavior was assessed following ASTM F2129 and no noticeable difference between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Indeed, several works investigating the microstructure of ECAPed UFG Ti report sub micrometer grain sizes and high dislocation densities. [27,30,31,33,34,36,37,40,41] An estimated density of 10 14 m À2 was calculated by Valiev et al [30] A nonuniform distribution of dislocations that tend to accumulate and tangle around grain boundaries was also observed in ECAPed UFG Ti. [35,39,62] This was confirmed in the current investigation, as shown by the TEM image in Figure 4.…”
Section: Non-uniform Distribution Of Dislocations In Ufg Timentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several works investigating the microstructure of ECAPed UFG Ti report sub micrometer grain sizes and high dislocation densities. [27,30,31,33,34,36,37,40,41] An estimated density of 10 14 m À2 was calculated by Valiev et al [30] A nonuniform distribution of dislocations that tend to accumulate and tangle around grain boundaries was also observed in ECAPed UFG Ti. [35,39,62] This was confirmed in the current investigation, as shown by the TEM image in Figure 4.…”
Section: Non-uniform Distribution Of Dislocations In Ufg Timentioning
confidence: 99%
“…[13,18,22] In recent years, investigations on the mechanical behavior of ultrafine-grained titanium (UFG Ti) processed by severe plastic deformation (SPD) have received considerable attention due to its potential applications, primarily in the biomedical field. However, these studies have either ignored [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] or merely superficially discussed [42][43][44] the possible occurrence of DSA. Serrations in stress-strain curves were never analyzed in the UFG Ti processed by equal channel angular pressing (ECAP) [27,28,[31][32][33]35,36,[38][39][40][41] or equal channel angular extrusion (ECAE), [34,37] even though they were observed.…”
Section: Introductionmentioning
confidence: 99%
“…According to the classic corrosion theory, the increased density of grain boundary and triple junction in nanostructures would have a detrimental effect on the overall electrochemical corrosion performance of NC metals. However, previous investigations on the electrochemical corrosion behavior of NC and ultrafine-grained (UFG) materials have shown many interesting results (Kim and Kim, 2013; Hajizadeh et al , 2015; Imantalab et al , 2016; Mendes Filho et al , 2010; Maleki et al , 2014). Some research demonstrated the electrochemical corrosion resistance of the metals was improved, such as NC Ni in 10Wt.% NaOH (Wang et al , 2006), NC FeAl alloy in 0.5 M H 2 SO 4 solution (Kedim et al , 2004), NC Zn-Ni alloy coating in 3Wt.% NaCl solution (Mosavat et al , 2012) and UFG Cu in 0.5 M HCl (Deng et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other works have been reported in the literature on a series combination of ECAP process with other SPD methods to enhance better biomedical titanium material properties. Mendes et al [49] studied microstructure and strength of CP-Ti grade2 under combined processes of warm ECAP at 4 passes, 300 o C then cold rolling (CR) at 70% reduction thickness. Results showed an increase of; tensile strength (from 408-796MPa), hardness (from 140-271HV) compared to annealed condition.…”
Section: Performance and Prospects Of Severe Plastic Deformation For mentioning
confidence: 99%